Mobile phones for the assessment of burns: we have the technology. Issue 11 (22nd October 2007) - Shokrollahi, Kayvan; Sayed, Mobin; Dickson, William; Potokar, Tom
Abstract : Objective: To investigate the accuracy of assessment of burn surface area and depth using a basic camera-equipped mobile phone. Methods: 31 patients with minor burns were assessed at the Welsh Centre for Burns & Plastic Surgery. Results: A high correlation was found between assessment of burn surface area and burn depth using a camera mobile phone compared with a live assessment. Conclusion: There are a number of implications for the use of mobile phone technology in hospitals and its potential use in the management of major in addition to minor burns, as well as other forms of trauma. The untapped potential for this technology in a hospital environment is highlighted.